2021
DOI: 10.24815/siele.v8i2.19240
|View full text |Cite
|
Sign up to set email alerts
|

Contemplating COVID-19 through disease and death in three short stories by Edgar Allan Poe

Abstract: Wort-case scenarios depicted in literary works may function to mourn and warn people about the real situation, such as the spread of COVID-19 that has altered worldwide life drastically. This study offers a reflection on the current pandemic time through a close reading of selected American classic literary works. The imagination of fear, isolation, and mask-wearing in Edgar Allan Poe’s short stories is resonant with the new expressions of the COVID-19 pandemic. Three short stories by Poe, i.e., ‘The Masque of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…On the other hand, one of the reasons for the phobic situation experienced by individuals is the “social distance rule” that should be followed to reduce the risk of transmission of COVID-19. It is observed that individuals’ reactions are similar to the previously mentioned phobic situations in the literature [ 7 ]. Further, it is a more appropriate conceptualization to express social distancing phobia due to this rule that individuals must comply with against the risk of virus transmission [ 8 , 9 ].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…On the other hand, one of the reasons for the phobic situation experienced by individuals is the “social distance rule” that should be followed to reduce the risk of transmission of COVID-19. It is observed that individuals’ reactions are similar to the previously mentioned phobic situations in the literature [ 7 ]. Further, it is a more appropriate conceptualization to express social distancing phobia due to this rule that individuals must comply with against the risk of virus transmission [ 8 , 9 ].…”
Section: Introductionsupporting
confidence: 58%
“…It is observed that individuals' reactions are similar to the previously mentioned phobic situations in the literature. 7 Further, it is a more appropriate conceptualization to express social distancing phobia due to this rule that individuals must comply with against the risk of virus transmission. 8,9 Phobias manifest as unusual fears of particular objects or situations.…”
Section: Introductionmentioning
confidence: 99%
“…In her study, Prasasti (2020) argues that EFL learners are managed to read a literary work critically by applying their literary competence, particularly by placing the meaning of certain figurative language in wider sociocultural contexts. Critical reading can be applied in a reading class employing a literary text, as such a text may serve as a sphere for readers to do a selfreflection (Dewi, 2021).…”
Section: Literary Competence In Critical Readingmentioning
confidence: 99%